EQ-5D-Y for the assessment of health-related quality of life among Taiwanese youth with mild-to-moderate chronic kidney disease. (13th February 2018) - Hsu, Chien-Ning; Lin, Hsiang-Wen; Pickard, A Simon; Tain, You-Lin
Abstract: Objective: To assess if health-related quality of life (HRQOL) of children with chronic kidney disease (CKD) and different comorbid conditions can be identified based on the EQ-5D child-friendly version (EQ-5D-Y). Design: Prospective cross-sectional study. Setting: A tertiary care medical center in Taiwan. Study participants: All CKD patients aged 7–18 years treated at the center between May 2014 and December 2016. Main Outcome Measures: HRQOL assessment was done using EQ-5D-Y. Spearman correlation tests were used for construct validity of the traditional Chinese version of EQ-5D-Y. Test-retest reliability was determined through Cohen's kappa values and intraclass correlation coefficients (ICC). Laboratory results and CKD-related morbid conditions were ascertained and assessed their associations with HRQOL score using multivariate linear regression. Results: Of 68 participants, 53 of them completed two HRQOL assessments of HRQOL at least 6-month. Cross-sectional analysis revealed fair to moderate correlations between EQ visual analogue score and patient characteristics. Older children at assessment ( P < 0.01), girls ( P = 0.03) and presence of mineral bone disorders had a significantly negative impact on HRQOL. Children self-reported EQ-5D-Y dimensions were found to be fairly to highly reliable (kappa = 0.2 to 0.8), except for 'pain/discomfort' and 'anxiety/depression'. Conclusions: The EQ-5D-Y discriminated among children with different level of CKD-related clinical burden, but the psychometric properties may be limited in some HRQOL dimensions. Further research will need to address factors that may threaten validity and reliability data provided by children and adolescents.